2023
DOI: 10.1152/japplphysiol.00024.2023
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Endurance triathlon competition shifts fecal metabolome independent of changes to microbiome composition

Abstract: Understanding changes to gut microbiota composition and metabolic output in response to acute exercise may be necessary for understanding the mechanisms mediating the long-term health and performance benefits of exercise. Our primary objective was to characterize acute changes in the fecal microbiome and metabolome following participation in an ultra-endurance (3.9km swim, 180.2km bike, 42.2km run) triathlon. An exploratory aim was to determine associations between athlete-specific factors (race performance [i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…We identified nine studies that evaluated α‐diversity of the gut microbiota before and after an acute exercise bout in human participants. Five of the nine studies reported no differences (Grosicki, Pugh, et al., 2023 ; Oliveira et al., 2022 ; Sato & Suzuki, 2022 ; Tabone et al., 2021 ; Zhao et al., 2018 ), which is consistent with observations from 6‐ to 8‐week training studies in humans (Allen et al., 2018 ; Cronin et al., 2018 ) and mice (Lamoureux et al., 2017 ) reporting no changes in α‐diversity. However, cross‐sectional investigations report greater α‐diversity in athletes and physically active individuals compared with sedentary controls (Clarke et al., 2014 ).…”
Section: Influence Of Acute Exercise On the Gut Microbiotasupporting
confidence: 73%
See 4 more Smart Citations
“…We identified nine studies that evaluated α‐diversity of the gut microbiota before and after an acute exercise bout in human participants. Five of the nine studies reported no differences (Grosicki, Pugh, et al., 2023 ; Oliveira et al., 2022 ; Sato & Suzuki, 2022 ; Tabone et al., 2021 ; Zhao et al., 2018 ), which is consistent with observations from 6‐ to 8‐week training studies in humans (Allen et al., 2018 ; Cronin et al., 2018 ) and mice (Lamoureux et al., 2017 ) reporting no changes in α‐diversity. However, cross‐sectional investigations report greater α‐diversity in athletes and physically active individuals compared with sedentary controls (Clarke et al., 2014 ).…”
Section: Influence Of Acute Exercise On the Gut Microbiotasupporting
confidence: 73%
“…Two investigations of acute exercise on microbiota responses (Grosicki, Pugh, et al., 2023 ; Oliveira et al., 2022 ), including our own (Grosicki, Pugh, et al., 2023 ), demonstrated no change in any bacterial species post‐exercise. While in contrast to many studies in this area, stability and resilience have been identified as essential ecological characteristics of the gut microbiota with relevance for human health (Fassarella et al., 2021 ).…”
Section: Influence Of Acute Exercise On the Gut Microbiotasupporting
confidence: 47%
See 3 more Smart Citations